2012
DOI: 10.1007/s00204-012-0929-9
|View full text |Cite
|
Sign up to set email alerts
|

The risky cocktail: what combination effects can we expect between ecstasy and other amphetamines?

Abstract: The recreational and illicit use of amphetaminic designer compounds, specially 3,4-methylenedioxymethamphetamine (MDMA; Ecstasy), is of concern worldwide. Such psychostimulating drugs are frequently present as complex mixtures in 'rave' pills, making concomitant polysubstance use a common trend. However, the understanding of possible combination effects with these substances is still scarce. The present study was aimed at predicting the cytotoxic effects of mixtures of four amphetaminic derivatives: MDMA, meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 62 publications
(59 reference statements)
2
26
0
Order By: Relevance
“…Of note is the fact that our data agrees well with a previous study that recently demonstrated that, in Hep G2 cells, four amphetamines that are frequently co‐ingested in ecstasy pills ( 4 ‐methylthioamphetamine, d ‐amphetamine, methamphetamine and MDMA) acted together producing additive cytotoxic mixture effects that could be accurately predicted by the CA model (Dias da Silva et al ., ) whereas the IA model failed to produce accurate estimations of the cytotoxic joint effects of that mixture.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note is the fact that our data agrees well with a previous study that recently demonstrated that, in Hep G2 cells, four amphetamines that are frequently co‐ingested in ecstasy pills ( 4 ‐methylthioamphetamine, d ‐amphetamine, methamphetamine and MDMA) acted together producing additive cytotoxic mixture effects that could be accurately predicted by the CA model (Dias da Silva et al ., ) whereas the IA model failed to produce accurate estimations of the cytotoxic joint effects of that mixture.…”
Section: Discussionmentioning
confidence: 97%
“…Whether the additivity herein observed extends to other combination ratios awaits further experimental confirmation. However, our previous work using this study model showed that different mixtures of amphetamine drugs, combined at different ratios, always produced additive effects (Dias da Silva et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we have previously tested the combined effects of commonly abused amphetamines in an in vitro model using human hepatoma Hep G2 cells. We demonstrated that, even when each component was present at very low concentrations, mixtures of these drugs had significant hepatotoxic effect (Dias da Silva et al ., ). We have now extended our previous research by applying this study model to hyperthermic conditions, which better reflect the physiological environment of the liver in an acute intoxication scenario, owing to the thermogenic action of the drugs and the environmental circumstances of the abuse.…”
Section: Introductionmentioning
confidence: 99%
“…37 °C) to highlight potential changes in cytotoxicity associated with an increase in body temperature. Furthermore, in a similar way to our previous study (Dias da Silva et al ., ), we tested the applicability of two mathematical models, concentration addition (CA) and independent action (IA), with the aim of investigating whether good agreement was still observed with the CA expectations, under the new experimental conditions. Finally, in order to delineate the mechanisms underlying the observed cytotoxicity, we further evaluated the involvement of several stress indicators in the promoted effects, namely the increased formation of reactive oxygen (ROS) and nitrogen (RNS) species, the contents of reduced (GSH) and oxidized (GSSG) glutathione, the loss of mitochondrial membrane potential (Δ ψm ), lipid peroxidation markers and the ATP intracellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, after exhaustive characterization of the toxicity profile of the single agents, the expected mixture effects were calculated, using the CA and IA approaches, and set as reference, as previously reported Dias da Silva et al 2013b). These concepts are based on general assumptions regarding the mechanisms of action of the mixture constituents and their details have been discussed elsewhere (Kortenkamp 2007).…”
Section: Prediction Of Mixture Effectsmentioning
confidence: 99%